Pemetaan Prakiraan Potensi Banjir di Papua Barat Menggunakan Model Builder Dalam Aplikasi Sistem Informasi Geografis (SIG) - Shelin Melinda; Nuryanto; Adriansyah (Buletin GAW Bariri, 2021)
Flood is a hydrometeorological disaster that often occurs in Indonesia. One of the causes of flooding is caused by extreme rainfall >100mm/day. West Papua Province is one of the regions in Indonesia that has a high intensity of rainfall throughout the year, making it vulnerable to potential flooding. To make it easier for people to know areas that have the potential for flooding, information such as a map of potential floods is needed. The use of Geographic Information Systems (GIS) in making flood potential maps can be useful for the community and certain institutions to make policies in flood disaster management. In this study to create a flood potential map, a software application, namely ArcGIS, is used, where in the software there are several tools that can be used to create command models, one of which is the model builder. The model builder then produces a spatial map output in the form of a flood potential forecast map in West Papua Province. From the results of regional mapping in West Papua Province, there are several regions or regencies in West Papua Province that have the potential for flood–prone areas in the Low – High category. The high intensity of rainfall in some areas or districts in West Papua has a high potential for flooding, especially in Sarong and Manokwari. Making this model builder can then be developed and can be used easily with modifications using Python.